Characteristics of the expression level of MMP-9 and TIMP-1 in hepatocellular and cholangiocellular liver carcinoma - V. A. Tumanskiy; M. D. Zubko (Zaporozhye State Medical University, 2015)
Aim. In order to determine the expression level of immunohistochemical markers of matrix metalloproteinase-9 (ММР-9) and its tissue inhibitor TIMP-1, and area of immunopositive cells а comprehensive histopathological, histological and immunohistochemical study of liver biopsy specimens was carried out in 94 patients, of which 55 (58.51%) patients had hepatocellular carcinoma and 39 (41.49%) - cholangiocellular carcinoma of liver. Methods and results. In 92.73% of patients with hepatocellular carcinoma and in 89.74% of patients with cholangiocellular carcinoma in malignant cells cytoplasmic expression of MMP-9 was determined. MMP-9 immunopositive cells took 59,33±22,57% of area of the tissue section of hepatocellular carcinoma and 52,71±20,86% of area of the tissue section of cholangiocellular liver cancer. In 80% of hepatocellular carcinoma patients and 74.36% of patients with cholangiocellular carcinoma in tumor cells cytoplasmic expression of TIMP-1 was revealed. TIMP-1 immunopositive cells constituted 21,94±6,27% of area of the tissue section of hepatocellular liver cancer and 33,05±13,85% of area of the tissue section of holangiocellular liver cancer. Conclusion. In both types of liver cancer direct strong relationship was noted between high levels of expression of MMP-9 by the tumor cells and low expression of TIMP-1, which indicates high invasive potential and aggressiveness of hepatocellular carcinoma and cholangiocellular carcinoma.